A Hierarchy of Central Places: A Spatial Analysis of Rural Service Centres in Man Basin. - Jadhav, A.S.; Ranadive, A.N. (National Geographical Journal of India, 2022)
The present study attempts to identify various rural service centres, classify them into different hierarchical orders and delineate their service region. For identifying the rural service centres, 16 critical services, forming six service groups have been taken into consideration. The place having 2500 and more population and at least three service groups has been identified as rural service centre. On the basis of weighted value of each function, the score value of each settlement has been calculated and categorised under different levels of hierarchy. Generally, rural service centre caters services to its surrounding area. For demarcating such service region. V.L.S. Prakash Rao’s formula is applied. The study reveals that the lower order service centres are located closely as compared to that of higher order service centres. It also reveals that, greater the functional magnitude of centre, larger is the area it serves. It is suggested that more service centres be developed in Jat and Man tahsils as the service centres are located far off villages